A study of roles and impact of project management consultancy in construction project - Nur Syahidah, Abu Bakar (2017)
This thesis is concerning on the role and effectiveness of Project Management Consultant (PMC) in Malaysia's construction industries. The objectives of this study is to identify the role of PMC and their effectiveness in managing construction projects. The thesis decscribes that there is misunderstanding about the general importance concepts in project management and the main objective that need to be achieved in management in the PMC's view. The lack of knowledge on the principles and techniques in project management also contribute to the problems already occurred. There are many parties that still confuse with the true meaning of the Project Management and Project Management Consultancy. The involvements of the Project Management Consultant in construction project often related to unsatisfaction and produce a low quality product of construction. This study focused on the scopes which is project management consultant firms that operates professionally, construction firms such as contractors, and individual professional such as civil engineers and project managers. When the objectives and scopes of study is set, then the data collection are made through two methods which is through literature review and a questionnaire survey. The data gained were then turned into results and analysis. From the analysis, the objectives of this study are achieved. This study has suggested roles need to be served by PMC and it found that PMC is very effective in managing construction project. The results of this study maybe able to correct the perception of PMC.